EFEKTIVITAS DAN KONTRIBUSI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KUTAI TIMUR - ELFREDA APLONIA LAU, SYAHRIANDI, LCA ROBIN JONATHAN (EKONOMIA, 2016)
SYAHRIANDI, Effectiveness and Revenue (PAD) of East Kutai Regency, under the guidance of Mr. LCA Robin Jonathan and Ec. Elfreda A. Lau.Reform of Local Finance has a chance to local governments to manage local financial independently. Financial management is none other than the management of the budget, including the management of revenue (PAD), which led to the fiscal independence to reduce fiscal dependence on the central government.The purpose of this study was to determine and analyze the contribution of Local Taxes, Retribuis Regional, Local Companies Gain, Other legitimate PAD to PAD East Kutai Regency for 2009, 2010, 2011, 2012 and 2013; to know and analyze the effectiveness of Local Taxes, Levies, Regional Companies Gain, Other legitimate PAD to PAD East Kutai Regency for 2009, 2010, 2011, 2012 and 2013.Grand theories of this research is financial management. The analytical tool used in this research is the analysis of the contribution and effectiveness ratio analysis.The results of this study indicate that the contribution of local taxes, levies, profit regional companies and other local revenue legitimate, once categorized in the criteria for contributions established by the Ministry of the Interior, it was concluded that the overall level of tax contribution, retribution , lapa regional companies and other legitimate PAD does not reach the level of the very good category. Kecuaili contribution rate other legitimate PAD in 2009 that reached the very good category. Efketivitas local taxes, levies, profit regional companies, and other local revenue legitimate, once categorized the effectiveness criteria set by the Ministry, it can be concluded that the overall level of effectiveness in the category very effective for local taxes, levies regional and other legitimate PAD.